2001
DOI: 10.1108/eum0000000006206
|View full text |Cite
|
Sign up to set email alerts
|

FM puzzle: sick building and Sydney’s open‐plan offices

Abstract: Presents analytical findings of sick building situations in Sydney’s open‐plan offices. Aims to ascertain facilities managers’ perceptions of sick building impacts on discrete aspects of workspace management, with a view to raising general awareness. A total of 100 open‐plan offices in the Sydney CBD were studied, and collated data analysed using partial correlation. Significant associations were found between sick building syndrome and certain aspects. However, management control played moderating roles in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…Menurut Silberman (1999), sindrom bangunan sakit boleh berlaku daripada pelbagai punca dan tiada penyebab khusus. Thac et al (2019) dan Ilozor et al (2001) menambah bahawa sindrom bangunan sakit adalah istilah yang merujuk kepada keadaan yang mana kombinasi pelbagai faktor seperti bahan kimia, asap dan komponen lain dari bahan binaan bangunan yang menyebabkan kualiti udara dalaman yang rendah menjurus kepada pelbagai masalah kesihatan. Keadaan sebegini telah menyebabkan Shaharuddin (1998) membezakan simptom-simptom bangunan sakit kepada empat kumpulan iaitu simptom kering (kering tekak dan mata, hidung tersumbat, kering kulit, sukar memakai lensa konteks mata), simptom alergi (hidung tersumbat, lelehan hidung, hidung terasa gatal, mata terasa gatal dan berair), simptom asma (ketegangan dada, nafas terengah-engah, susah bernafas) dan simptom berpunca dari sebab yang tak pasti (lemah dan lesu, sakit kepala).…”
Section: Kajian Literaturunclassified
“…Menurut Silberman (1999), sindrom bangunan sakit boleh berlaku daripada pelbagai punca dan tiada penyebab khusus. Thac et al (2019) dan Ilozor et al (2001) menambah bahawa sindrom bangunan sakit adalah istilah yang merujuk kepada keadaan yang mana kombinasi pelbagai faktor seperti bahan kimia, asap dan komponen lain dari bahan binaan bangunan yang menyebabkan kualiti udara dalaman yang rendah menjurus kepada pelbagai masalah kesihatan. Keadaan sebegini telah menyebabkan Shaharuddin (1998) membezakan simptom-simptom bangunan sakit kepada empat kumpulan iaitu simptom kering (kering tekak dan mata, hidung tersumbat, kering kulit, sukar memakai lensa konteks mata), simptom alergi (hidung tersumbat, lelehan hidung, hidung terasa gatal, mata terasa gatal dan berair), simptom asma (ketegangan dada, nafas terengah-engah, susah bernafas) dan simptom berpunca dari sebab yang tak pasti (lemah dan lesu, sakit kepala).…”
Section: Kajian Literaturunclassified
“…Other factors that have been implicated include noise, artificial lighting, static electricity, ions, electromagnetic fields and psychological effects (Thomas-Mobley, Roper & Oberle, 2005). Ilozor et al (2001) found that volatile organic compounds (VOC's), synthetic compounds, biological bacteria, fungi, molds and viruses are readily found in emissions from office equipment, building materials, dust, cigarettes and office supplies such as solvents, glues and cleaning agents for interior workspaces. Many large offices are air-conditioned but these installations rarely work well making it either too hot or too cold.…”
Section: Components Of Sick Building Syndromementioning
confidence: 99%
“…The many symptoms of SBS include tired or strained eyes (Aerias Air Quality Sciences, 2010), unusual tiredness (Pitt, 2008;Rooley, 1995), fatigue or drowsiness (National Safety Council, 2010), headaches (Boykin & Sauer, 1996;Muzi, Abbritti, Accattoli & dell' Omo, 1997), tension (Yu et al, 2009), irritability or nervousness (US Environmental Protection Agency, 2012), sinus congestion (Bachmann, Turck & Myers, 1995), chest tightness (Aerias Air Quality Sciences, 2010; Muzi et al, 1997), wheezing (Global Healing Centre, 2012), skin dryness Muzi et al, 1997) and gastrointestinal complaints (Pitt, 2008). These symptoms were summarized by the World Health Organization (WHO) in its June 1982 report (Brown, 2004;Boykin & Sauer, 1996;Fernberg, 1989;Ilozor et al, 2001;Rooley, 1995). SBS occurs in a workspace where a significant number of occupants complain of sickness and/or discomfort.…”
Section: Symptoms Of Sick Building Syndromementioning
confidence: 99%
See 2 more Smart Citations